Construction and Evaluation of a Multipurpose Performance Check Phantom for Computed Tomography - L.E. Lubis; I. Hariyati; D. Ryangga; I.A.S. Mu'minah; T. Mart; D.S. Soejoko (PPIKSN-BATAN, 2020)
The use of computed tomography (CT) has become a common practice in medical diagnosis in Indonesia. Its number, however, is not matched by the availability of dedicated-performance-check phantoms. This paper aims to describe the design, construction, and evaluation of an in-house phantom for CT performance check that accommodates both radiation dose measurement and image quality performance checks. The phantom is designed as laser-cut polymethyl methacrylate (PMMA) slabs glued together to form a standard cylindrical shape, with spaces to place dose measurement and image quality modules. In this paper, measurement results on both aspects are discussed and compared with standard phantoms and other works. For dose measurement, the constructed phantom exhibited the greatest absolute discrepancy against the reference standard phantom of 8.89 %. Measurement of the CT number linearity and modulation transfer function (MTF) yielded, at most, 7.51 % and 5.07 % discrepancies against Catphan 604, respectively. Meanwhile, although found to be more linear in the phantom-based contrast linearity test, the use of the in-house phantom for clinical image contrast threshold determination requires further study. For noise power spectrum (NPS) measurement, accurate results were obtained within a limited range of spatial frequency.